The Japanese Saving Rate - Chen, Kaiji; İmrohoroğlu, Ayşe and İmrohoroğlu, Selahattin (American Economic Review, 2006)
Despite much work, economists have not been able to quantitatively account for the differences in the Japanese and U.S. saving rates after World War II. In this paper, we show that the use of actual Japanese total factor productivity growth rates in a standard growth model generates saving rates that are reasonably similar to the Japanese data between 1956 and 2000. (JEL E21, E22, O41, O47)